Treinamento individualizado aeróbio, resistido e concorrente: efeitos sobre os marcadores de estresse oxidativo em ratos Wistar - Costa Júnior, Marcelo [UNESP] (2013)
This study aimed to investigate the effect of aerobic training, resistance and concurrent oxidative stress in rats. Therefore, we used Wistar rats during eight weeks of physical training. Initially all animals were submitted to lactate minimum tests to identify the lactate minimum during swimming exercise and 5-RM test for assessment of the submaximal force. The animals were divided into four groups: control, aerobic, resistance and concurrent (combination of aerobic and resistance protocols in the same session) conducted five days a week for eight weeks They were adapted to liquid medium to minimize stress. All training protocols were performed with individual overstraining, establishing periodization during the eight weeks, which consisted of gradual increase of intensity during the microcycles. In the fourth and eighth weeks, the animals were submitted to a period of polishing (volume reduction with maintenance of the intensity) to promote overcompensation. At the end of the experimental period were analyzed: antioxidant enzymes, biomarkers of oxidative stress in muscle tissue and erythrocytes. About oxidative enzymes, no significant differences were found for TBARS in any of the experimental groups, but there was an increase in the activity of glutathione peroxidase and superoxide dismutase in all trained groups. By contrast, catalase activity did not change during the eight weeks of training. Therefore, all three physical training protocols promote increase of antioxidant enzymes without changing the markers pro - oxidants and changes in redox balance